Analisis Sistem Intensity Modulation – Direct Detection (IM-DD) Radio Over Fiber (ROF) Dengan Teknik Direct Modulation - Muhammad Arifiansyah Brahma Brata; Sholeh Hadi Pramono; Sapriesty Nainy Sari (Jurnal Mahasiswa TEUB, 2017)
Teknologi Radio Over Fibre (RoF) menggunakan medium berupa fiber optik untuk mendistribusikan RF carrier (Radio Frequency) dari lokasi pusat (headend) ke Remote Antenna Units (RAUs). RoF memungkinkan untuk memusatkan pemrosesan RF carrier pada satu lokasi (headend) dan kemudian menggunakan fiber optik. Salah satu jenis RoF adalah IM-DD RoF. Teknik yang paling mudah untuk mentransmisikan RF carrier secara optikal adalah dengan modulasi direct. akan tetapi modulasi direct memiliki beberapa kekurangan pada sistem IM- DD ROF, salah satunya adalah kesulitan untuk penggunaan frekuensi tinggi atau frekuensi mm-wave ..Berdasarkan permasalahan itu, dirancang sebuah sistem komunikasi IM-DD RoF pada modulasi direct dengan menggunakan software Optisystem dan menganalisis sistem terhadap parameter-parameter seperti BER, Q-Factor, dan Eye Height. Berdasarkan hasil simulasi pengaruh format line coding NRZ pada panjang fiber optic link 11 km, RF carrier 3,65 GHz, dan bit rate 2,5 Gbps, didapatkan nilai BER , Q-Factor 6,33326, dan Eye Height 0,000655. Kata kunci: Radio Over Fibre, IM-DD ROF, directly modulated ROF link, Radio-over-Fibre (RoF) technology entails the use of optical fibre links to distribute RF signals from a central location (headend) to Remote Antenna Units (RAUs). In narrowband communication systems and WLANs, RF signal processing functions such as frequency up-conversion, carrier modulation, and multiplexing, are performed at the BS or the RAP, and immediately fed into the antenna. RoF makes it possible to centralise the RF signal processing functions in one shared location (headend), and then to use optical fibre,One type of RoF is IM- DD RoF. The easiest technique to transmit RF carrier in optical domain is by using direct modulation. But Direct Modulation has some drawbacks on ROF's IM-DD system, one of which is the difficulty to use high frequency or mm-wave frequency. Based on that problem, RoF IM-DD communication system on direct modulation had been designed using Optisystem’s software and Analyze the System using the parameters such as BER, Q-Factor, and Eye Height.according to the data simulation of the effect of NRZ line coding format on fiber link length of 11 km, RF carrier of 3,65 GHz, and bit rate of 2,5 Gbps, the value of BER that had been obtained is , Q- Factor of 6,33326, and the Eye Height of 0,000655. Keywords : Radio Over Fibre, IM-DD ROF, ROF